2019
DOI: 10.1002/jcb.29270
|View full text |Cite
|
Sign up to set email alerts
|

miR‐23b‐3p regulates apoptosis and autophagy via suppressing SIRT1 in lens epithelial cells

Abstract: Age-related cataract is one of the prior causes of blindness and the incidence rates of cataract are even rising. Oxidative stress plays an important role in the pathogenesis of cataracts. Under oxidative stress, lens epithelial cell (LEC cell) apoptosis is activated, which might lead to the opacity of the lens and accelerate the progression of cataract development. Meanwhile, autophagy is also active to face oxidative stress. miRNAs have been reported to involve cataract. However, the underlying mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
2
23
0
1
Order By: Relevance
“…Further evidence has suggested that the SIRT1 3′ UTR is critical for SIRT1 mRNA stability. Additionally, a series of miRNAs, including miR-132-3p, miR-23b-3p, and miR-34a, were found to modulate SIRT1 expression [9,14,15]. Our results demonstrated that miR-155 upregulation inhibited SIRT1 expression and HUVEC proliferation and promoted TNF-α-induced senescence in HUVECs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Further evidence has suggested that the SIRT1 3′ UTR is critical for SIRT1 mRNA stability. Additionally, a series of miRNAs, including miR-132-3p, miR-23b-3p, and miR-34a, were found to modulate SIRT1 expression [9,14,15]. Our results demonstrated that miR-155 upregulation inhibited SIRT1 expression and HUVEC proliferation and promoted TNF-α-induced senescence in HUVECs.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports have shown that the SIRT1 3′-untranslated region (3′ UTR) is critical for its mRNA stability. Additionally, a series of microRNAs (miRNAs), such as miR-34a, miR-23b-3p, and miR-132-3p, modulate SIRT1 expression [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The previous morphological study found that, during encystment of P. cristata, cytoplasmic structures such as extrusomes were wrapped in membrane vesicles to form autophagic vesicles or autophagosomes in the intracellular self-digestion phenomenon [15]. Scientists found that knockdown of miR-23b-3p expression in LEC cells elevated autophagy significantly during hydrogen peroxide stress [16]. We found that miR-23b-3p was downregulated during the cyst formation.…”
Section: Discussionmentioning
confidence: 65%
“…МикроРНК-23b, в отличие от вышеописанных микроРНК-20а и -21, является опухолевым супрессором, ингибируя посредством влияния на гены-мишени SRC и AKT1 клеточную пролиферацию, миграцию и инвазию, а также индуцируя остановку клеточного цикла в стадии G0/G1 [25]. Наши данные согласуются с представлением других исследователей о роли этого онкомаркера.…”
Section: Discussionunclassified